Feminist agenda and awareness:: Analysis of @modernadepueblo’s reels - Abellán-Hernández, María; Centenero de Arce, María José (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
This study examines how social networks, particularly the @modernadepueblo Instagram profile, challenge conventional feminine ideals. By analyzing reels through the lens of the feminist agenda 2030, it explores how these digital narratives deconstruct traditional gender representations. The methodology assesses the content's alignment with sustainable feminist objectives and its impact on the digital audience. Results indicate that the reels present alternative images of femininity, employing a critical and ironic tone characteristic of the millennial generation. Social networks thus emerge as spaces for questioning and reshaping collective imaginaries around gender.